Exploring Chalcone Derivatives Against Alzheimer’s Disease: Biological Activity and Structure–Activity Relationships - Prabha, Shashi; Rajput, Sobhit Singh (Synlett, 2025)
Chalcone is a versatile scaffold that has gained attention for its potential in developing treatments for Alzheimer’s disease (AD). This review highlights recent progress in the design and evaluation of chalcone hybrids and derivatives with anti-Alzheimer activity, particularly against key enzymes such as acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and monoamine oxidases (MAO-A and MAO-B). Many of these compounds show promising inhibition, suggesting their potential to improve cholinergic transmission and reduce neurodegeneration. Structure–activity relationship (SAR) studies reveal that substitution patterns on aromatic rings strongly influence activity. Oxindole-based chalcone analogues (5) were good AChE inhibitors, while chalcone–rivastigmine hybrids (11) were excellent BChE inhibitors. For MAO-B, 4-aminochalcone–rivastigmine hybrids (10) and morpholine-based chalcone hybrids (20) were potent inhibitors. Molecular docking studies further explain how these molecules interact with target enzymes, supporting their biological relevance. The combination of pharmacophores with the chalcone core has also improved selectivity and potency. Overall, the findings summarized in this review suggest that chalcone-based compounds are promising candidates for further development as anti-Alzheimer agents. With their multitarget potential and ease of structural modification, chalcones represent a valuable pharmacophore for addressing the complex pathology of AD. Future work focusing on rational design and computational tools may enable the discovery of effective therapies.
Keywords: Alzheimer’s disease; Acetylcholinesterase; Hybrids; Chalcone; Docking